2014
DOI: 10.1039/c3cy01000g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and high-throughput testing of multilayered supported ionic liquid catalysts for the conversion of CO2 and epoxides into cyclic carbonates

Abstract: Multilayered covalently supported ionic liquid phase (mlc-SILP) materials were synthesised by grafting\ud different bis-vinylimidazolium salts on thiol-functionalised silica. These materials, which contain a crosslinked\ud oligomeric network of imidazolium units, were characterised and tested as catalysts for the reaction\ud of carbon dioxide with various epoxides to produce cyclic carbonates. The materials prepared by\ud supporting a bis-imidazolium iodide salt with xylene or octane as a linker between the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 37 publications
3
56
1
1
Order By: Relevance
“…The Brunauer-Emmet-Teller (BET) specific surface area (180 m 2 /g) as well as the absence of a narrow pore size distribution obtained for the SImCat, can be attributed to the presence of the organic polymeric matrix inside the solid. The observed BET value is similar to those reported for other porous 60 silica architectures covered by polymeric cross-linked organic shell9,10, 13,17,41, 65 . The type 3 hysteresis loop observed at high P/P 0 can be ascribed to a large meso-macro porosity arising from interparticles interaction.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The Brunauer-Emmet-Teller (BET) specific surface area (180 m 2 /g) as well as the absence of a narrow pore size distribution obtained for the SImCat, can be attributed to the presence of the organic polymeric matrix inside the solid. The observed BET value is similar to those reported for other porous 60 silica architectures covered by polymeric cross-linked organic shell9,10, 13,17,41, 65 . The type 3 hysteresis loop observed at high P/P 0 can be ascribed to a large meso-macro porosity arising from interparticles interaction.…”
supporting
confidence: 86%
“…The first catalytic test was 45 performed selecting the initial pressure of 50 bar. It is worth to underline that the TON value obtained under these conditions (TON = 136) is one of the highest reported in literature for supported heterogeneous systems 9 . An increase of the working pressure to 70 bar, while keeping constant the temperature at 150 50 °C (Table 1, entry 2), did not substantially improve the catalytic performances.…”
Section: Catalytic Testsmentioning
confidence: 63%
“…Cationic moieties are frequently based on alkylammonium, pyridinium or imidazolium salts. However, imidazolium salts have some additional advantages as they display catalytic activity [43][44][45][46][47] and an ability to be transformed into N-heterocyclic carbenes to coordinate metals [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…The materials 20b and 21b, having octane and p-xylene as linker, respectively, and iodide as counterion, were identified as the most active catalysts. These results indicated that the leaving ability of the halide played a role in determining the reaction rate and that a better separation between the imidazolium units, obtained with the linker with the longest chain (octane), could prove favourable In 2014, a series of multilayered covalently-supported ionic liquid phase (mlc-SILP) materials 18, 19a-b, 20a-b, 21a-b were synthesised by grafting different bis-vinylimidazolium salts on thiol-functionalised silica (Scheme 9) [17]. Covalently-supported imidazolium salts represent an interesting class of recyclable catalysts with excellent stability and durability [18,19].…”
Section: Synthesis Of Cyclic Carbonatesmentioning
confidence: 99%
“…Finally, the catalytic activity of Poly(mVIm + I − ) was very low, despite the higher concentration of active sites, as a consequence of the absence of porosity and then of the low accessibility to the active sites. In 2014, a series of multilayered covalently-supported ionic liquid phase (mlc-SILP) materials 18, 19a-b, 20a-b, 21a-b were synthesised by grafting different bis-vinylimidazolium salts on thiolfunctionalised silica (Scheme 9) [17]. Covalently-supported imidazolium salts represent an interesting class of recyclable catalysts with excellent stability and durability [18,19].…”
Section: Synthesis Of Cyclic Carbonatesmentioning
confidence: 99%